1985
DOI: 10.1055/s-2007-1014073
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Risk Factors Related to Early Mortality Following Combined Mitral Valve Replacement and Coronary Artery Bypass Grafting

Abstract: Combined mitral valve replacement (MVR) and coronary artery bypass graft (CABG) operation was performed in 62 consecutive patients at the Wessex Cardiothoracic Centre, Southampton, from 1972 to 1983. There were 43 men and 19 women. The mean age was 61 years. Ten patients were in New York Heart Association (NYHA) functional class II, 34 in class III and 18 were in functional class IV. Mitral regurgitation was predominant in 50 patients and mitral stenosis in 12. Emergency operations were performed in 9 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They concluded that, where concomitant mitral valve and coronary disease exist, it is essential to revascularizc the myocardium. In another report on combined mitral valve and coronary disease, it was con cluded that preoperativc NYHA functional class and emergency operations significantly influenced surgical survival [10], Yadav et al [14] have shown a 13% mortality when the mitral valve disease was ischemic in origin while there was no mortality when the origin was rheumatic disease. It has also been re ported that advanced age [14,15] and NYHA were the highest predictors for mortality [7], Very few reports of multiple valve replace ments combined with CABG are available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, where concomitant mitral valve and coronary disease exist, it is essential to revascularizc the myocardium. In another report on combined mitral valve and coronary disease, it was con cluded that preoperativc NYHA functional class and emergency operations significantly influenced surgical survival [10], Yadav et al [14] have shown a 13% mortality when the mitral valve disease was ischemic in origin while there was no mortality when the origin was rheumatic disease. It has also been re ported that advanced age [14,15] and NYHA were the highest predictors for mortality [7], Very few reports of multiple valve replace ments combined with CABG are available in the literature.…”
Section: Discussionmentioning
confidence: 99%